VARIASI DAN PERSEBARAN PISANG DI PENGUNUNGAN ARFAK - Maria Sadsoeitoeboen; Fajar R.N. Sianipar; Paskalina Th. Lefaan; Johanis P. Kilmaskossu; Janry I. Loupatty; Ketura A. Dimara; Debora Stevany (FMIPA Universitas Papua, 2021)
The Arfak Mountains are a group of mountains located in the Bird's Head, Papua Island (New Guinea), which can reach a height of 2,950 m above sea level. Based on the information found several cultivars of bananas and wild bananas. However, information about the number of variations and distribution of bananas in the Arfak Mountains has not been widely studied. This study aims to determine the variation and distribution of bananas in the Arfak Mountains. The study was conducted on August 29, 2021 – October 23, 2021 in Anggigida District, Warmare District, Minyambouw District, and Anggi District. Data collection used a survey method. The results of the study concluded that there were 14 cultivars and 4 types of wild bananas. In addition, there were variations of domesticated banana plants on the Ransiki-Anggi route and the Warmare-Anggi route. 3 species of wild bananas were only found on the Warmare-Anggi route. Especially the wild banana Musa ingens which was found growing on the left and right of the road along Ransiki to Anggi had a male flower/melanset heart (Lanceolate) while on the left-right side of the road along Warmare to Anggi it had the shape of the male flower / heart is rounded (Rounded).